Business Judgment Rule in the Amendment of the State-Owned Enterprises Law - Habibie, Muhammad Mirza; Catur Rini, Yuliani; Winkar Setya, Kartika; Sukirno (Jurnal Hukum In Concreto, 2025)
The third amendment to the BUMN Law marks a new paradigm in BUMN management, adopting the Business Judgment Rule (BJR) doctrine. The material of the amendment is that BUMN directors cannot be held legally responsible for losses that occur if it is proven that the loss was not caused by error or negligence, decisions were taken in good faith and caution, there was no conflict of interest, and preventive measures were taken to prevent or stop losses. This BJR changes the pattern of directors' accountability, BUMN losses are no longer considered state financial losses so that they are not included in the realm of corruption based on the Corruption Law, this study uses a normative legal method through a doctrinal and conceptual approach, and uses secondary data. The analysis used uses the deductive method. With the amendment to the Law, it provides guidance for directors to be more careful in carrying out BUMN business processes. Providing certainty to corporate directors professionally without being overshadowed by fear of criminalization.